Morphological rearrangement of the metabolic link of the microcirculatory bed of guinea pigs lungs after sensitization with ovalbumin - S. S. Popko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The reaction of the lung microvessels is an urgent issue of morphology and medicine in general, as well as one of the insufficiently investigated points in the study of morphological changes in chronic allergic diseases of the respiratory system.